Coated asphalt for negative electrode of new energy battery as well as preparation method and application of coated asphalt

By using ethylene tar raw materials and crosslinking agents in the negative electrode materials of new energy battery, the problem of high quinoline insoluble content in existing coated asphalt was solved, and the coated asphalt with high softening points and low quinoline insoluble content was achieved, which improved the electrochemical performance and resource utilization efficiency of the battery.

CN119823780APending Publication Date: 2025-04-15YICHUN YINGKE CARBON MATERIALS TECHNOLOGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411195272.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing coated asphalt has a high quinoline insoluble content in the negative electrode materials of new energy battery, resulting in low electrochemical capacity and low resource utilization efficiency.

Method used

By mixing the ethylene tar raw material with a crosslinking agent, a hydroxide crosslinking reaction is performed under an oxygen-containing atmosphere, and then the crosslinking reaction is continued in a protective gas atmosphere, and finally a coated asphalt with high softening points and low quinoline insoluble matter is obtained through liquid phase volatilization.

Benefits of technology

The first efficiency, reversible capacity and circulation of the negative electrode of the new energy battery are improved, the content of quinoline insoluble matter coated asphalt is reduced, and the efficiency of resource utilization is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823780A_ABST
    Figure CN119823780A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy battery materials, and particularly relates to coated asphalt for a negative electrode of a new energy battery as well as a preparation method and application of the coated asphalt. The method comprises the following steps: mixing an ethylene tar raw material and a cross-linking agent, and carrying out a first hydroxide cross-linking reaction in an oxygen-containing atmosphere to obtain a reaction liquid after the first hydroxide cross-linking reaction; transferring the reaction liquid after the first hydroxide cross-linking reaction into a protective gas atmosphere, and carrying out a second hydroxide cross-linking reaction to obtain a reaction liquid after a second hydroxide cross-linking reaction; and cooling the reaction liquid after the second hydroxide cross-linking reaction to room temperature, and performing liquid phase volatilization, so that the obtained coated asphalt has the characteristics of high softening point, low quinoline insoluble content, low coating thickness, high integrity, high compactness and high yield, is easy to realize industrial application, and can solve the recycling problem of ethylene tar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy battery materials, and specifically relates to a coated asphalt for a negative electrode of a new energy battery, and a preparation method and application thereof. Background Art

[0002] In recent years, driven by the development of new energy vehicles, the market demand for coated asphalt for the modification of negative electrode materials for lithium-ion batteries has great prospects. The raw material for industrial production of coal-based coated asphalt is coal tar. Since the polycyclic aromatic hydrocarbons in coal tar have a dense structure and almost no branched free radicals, the coking value of the coated asphalt prepared by it is high. However, due to the molecular structure of its tightly connected polycyclic aromatic hydrocarbons, the quinoline insoluble content of the coated asphalt prepared by it is relatively high, generally greater than 15%. The electrochemical capacity of the negative electrode material of the coal-based coated asphalt with high quinoline insoluble content is low after coating graphite. Ethylene tar is currently mainly used to produce petroleum naphthalene and methylnaphthalene, and the residual oil is often used as boiler fuel, resulting in low added value utilization of resources. At present, the high softening point of the coated asphalt and the high quinoline insoluble matter coexist, and the high quinoline insoluble matter will reduce the fluidity and wettability of the coated asphalt, thereby affecting the electrochemical performance of new energy batteries. Summary of the invention

[0003] In view of this, the purpose of the present invention is to provide a coated asphalt for the negative electrode of a new energy battery and a preparation method and application thereof. The coated asphalt prepared by the present invention has the characteristics of high softening point and low quinoline insolubles, and can improve the initial efficiency, reversible capacity and cyclability of the negative electrode of the new energy battery.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing coated asphalt for a negative electrode of a new energy battery, comprising the following steps:

[0006] The ethylene tar raw material and the cross-linking agent are mixed, and a first hydrogen oxidation and cross-linking reaction is carried out in an oxygen-containing atmosphere to obtain a reaction liquid after the first hydrogen oxidation and cross-linking reaction;

[0007] Transferring the reaction liquid after the first hydrogenation and cross-linking reaction into a protective gas atmosphere to carry out a second hydrogenation and cross-linking reaction to obtain a second hydrogenation and cross-linking reaction reaction liquid;

[0008] After the reaction liquid after the second hydrogen oxidation and cross-linking reaction is cooled to room temperature, liquid phase volatilization is performed to obtain coated asphalt for the negative electrode of new energy batteries.

[0009] Preferably, the ethylene tar feedstock includes full-component ethylene tar or heavy ethylene tar.

[0010] Preferably, the cross-linking agent comprises a mixture of dicyclic aromatic hydrocarbons and anhydrous ethanol; the dicyclic aromatic hydrocarbons comprise one or more of naphthalene compounds, acenaphthene compounds and azulene compounds.

[0011] Preferably, the oxygen-containing atmosphere is a mixed atmosphere of oxygen and air; the volume fraction of oxygen in the mixed atmosphere is 0 to 50%.

[0012] Preferably, based on the total mass of the ethylene tar raw material and the cross-linking agent, the flow rate of the oxygen-containing atmosphere is 0.1 to 5 L / min / kg.

[0013] Preferably, the temperature of the first hydrogenation cross-linking reaction is 340-380° C., and the insulation time is 1-4 hours.

[0014] Preferably, the protective gas is nitrogen or argon; based on the total mass of the ethylene tar raw material and the cross-linking agent, the flow rate of the protective gas is 0.1 to 5 L / min / kg.

[0015] Preferably, the temperature of the second hydrogenation cross-linking reaction is 340-380° C., and the insulation time is 0.5-2 h.

[0016] The present invention also provides coated asphalt for the negative electrode of a new energy battery prepared by the preparation method described in the above technical scheme, wherein the softening temperature of the coated asphalt for the negative electrode of a new energy battery is ≥180°C, and the mass percentage of quinoline insoluble matter is ≤1%.

[0017] The present invention also provides the use of the coated asphalt for the negative electrode of a new energy battery described in the above technical solution in the negative electrode of a new energy battery.

[0018] The present invention provides a method for preparing coated asphalt for the negative electrode of a new energy battery, comprising the following steps: mixing an ethylene tar raw material and a cross-linking agent, performing a first hydrogen oxidation and cross-linking reaction in an oxygen-containing atmosphere to obtain a first hydrogen oxidation and cross-linking reaction reaction liquid; transferring the first hydrogen oxidation and cross-linking reaction reaction liquid to a protective gas atmosphere to perform a second hydrogen oxidation and cross-linking reaction to obtain a second hydrogen oxidation and cross-linking reaction reaction liquid; cooling the second hydrogen oxidation and cross-linking reaction reaction liquid to room temperature, and then performing liquid phase volatilization to obtain a coated asphalt for the negative electrode of a new energy battery.

[0019] In the first stage of the present invention, the ethylene tar raw material undergoes a condensation reaction under the action of a cross-linking agent to form a longer chain structure, and then a hydrogenation cross-linking reaction occurs under the action of oxygen. In the second stage, the protective gas pressurization can bring out the excess free oxygen in the mixture, which can improve the softening point and wettability of the coated asphalt, while reducing the content of quinoline insolubles. The method has a short process flow, low operating cost, and short production time. The prepared coated asphalt has the characteristics of high softening point, low quinoline insolubles, low coating thickness, high integrity, high density and high yield, and is easy to realize industrial application, promote the high value utilization of industrial ethylene tar, and can solve the resource problem of ethylene tar. In addition, the coated asphalt prepared by the present invention is used in the negative electrode of new energy batteries to improve the first efficiency (≥87%), reversible capacity (≥330mA·h / g), and cyclicity (the number of cycles after coating asphalt is increased by ≥10%), which can improve the electrochemical performance of new energy batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a physical picture of the coated asphalt for the negative electrode of a new energy battery prepared in Example 1 of the present invention;

[0021] Figure 2 This is a transmission electron microscope image of the coated asphalt for the negative electrode of the new energy battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention provides a method for preparing coated asphalt for a negative electrode of a new energy battery, comprising the following steps:

[0023] The ethylene tar raw material and the cross-linking agent are mixed, and a first hydrogen oxidation and cross-linking reaction is carried out in an oxygen-containing atmosphere to obtain a reaction liquid after the first hydrogen oxidation and cross-linking reaction;

[0024] Transferring the reaction liquid after the first hydrogenation and cross-linking reaction into a protective gas atmosphere to carry out a second hydrogenation and cross-linking reaction to obtain a second hydrogenation and cross-linking reaction reaction liquid;

[0025] After the reaction liquid after the second hydrogen oxidation and cross-linking reaction is cooled to room temperature, liquid phase volatilization is performed to obtain coated asphalt for the negative electrode of new energy batteries.

[0026] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used in the preparation, and commercially available products known to those skilled in the art can be used.

[0027] The present invention mixes ethylene tar raw material and a crosslinking agent, performs a first hydrogen oxidation and crosslinking reaction in an oxygen-containing atmosphere, and obtains a reaction liquid after the first hydrogen oxidation and crosslinking reaction.

[0028] In the present invention, the ethylene tar raw material preferably includes full-component ethylene tar or heavy ethylene tar, more preferably full-component ethylene tar; the heavy ethylene tar is preferably ethylene tar after naphthalene and methylnaphthalene are extracted.

[0029] In the examples of the present invention, the properties of the full-component ethylene tar used are shown in Table 1.

[0030] Table 1 Characteristics of all components of ethylene tar

[0031]

[0032] In the present invention, the cross-linking agent preferably comprises a mixture of dicyclic aromatic hydrocarbons and anhydrous ethanol; the dicyclic aromatic hydrocarbons preferably comprise one or more of naphthalene compounds, acenaphthene compounds and azulene compounds, more preferably naphthalene, acenaphthene or azulene; the mass ratio of the dicyclic aromatic hydrocarbons to anhydrous ethanol is preferably 5 to 10:1, more preferably 6 to 8:1; the mass ratio of the ethylene tar raw material to the cross-linking agent is preferably 100:1 to 5, more preferably 100:2 to 4.

[0033] In the present invention, the oxygen-containing atmosphere is preferably a mixed atmosphere of oxygen and air; the volume fraction of oxygen in the mixed atmosphere is preferably 0 to 50%, more preferably 10 to 30%; based on the total mass of the ethylene tar feedstock and the cross-linking agent, the flow rate of the oxygen-containing atmosphere is preferably 0.1 to 5 L / min / kg, more preferably 1 to 3 L / min / kg.

[0034] In the present invention, the temperature of the first hydrogen oxidation and cross-linking reaction is preferably 340-380°C, more preferably 350-370°C, and the insulation time is preferably 1-4h, more preferably 2-3h; the first hydrogen oxidation and cross-linking reaction is preferably carried out in a reactor; the pressure in the reactor is preferably 0.1-1.5MPa, more preferably 0.5-1.0MPa; the first hydrogen oxidation and cross-linking reaction is preferably carried out under stirring; the stirring rate is preferably 100-300r / min, more preferably 150-250r / min.

[0035] In the first hydrogen oxidation cross-linking reaction process, the ethylene tar raw material undergoes a condensation reaction under the action of the cross-linking agent to form a longer chain structure, and then undergoes a hydrogen oxidation cross-linking reaction under the action of oxygen. The anhydrous ethanol in the cross-linking agent can promote the mutual combination of free radicals at the ends of the polycyclic aromatic hydrocarbon chains, thereby increasing the condensation degree of the polycyclic aromatic hydrocarbons and reducing the reaction temperature of the cross-linking reaction.

[0036] After obtaining the reaction liquid after the first hydrogen oxidation and cross-linking reaction, the present invention transfers the reaction liquid after the first hydrogen oxidation and cross-linking reaction to a protective gas atmosphere to carry out a second hydrogen oxidation and cross-linking reaction to obtain a second hydrogen oxidation and cross-linking reaction reaction liquid.

[0037] In the present invention, the protective gas is preferably nitrogen or argon; based on the total mass of the ethylene tar raw material and the cross-linking agent, the flow rate of the protective gas is preferably 0.1 to 5 L / min / kg, more preferably 0.5 to 3 L / min / kg.

[0038] In the present invention, the temperature of the second hydrogen oxidation and cross-linking reaction is preferably 340-380°C, more preferably 350-370°C, and the insulation time is preferably 0.5-2h, more preferably 0.5-1h; the second hydrogen oxidation and cross-linking reaction is preferably carried out in a reactor; the pressure in the reactor is preferably 0.1-1.5MPa, more preferably 0.5-1.0MPa; the second hydrogen oxidation and cross-linking reaction is preferably carried out under stirring; the stirring rate is preferably 100-300r / min, more preferably 150-250r / min.

[0039] During the second hydrogen oxidation and cross-linking reaction of the present invention, pressurizing a protective gas such as nitrogen can remove excess free oxygen in the mixture obtained from the first hydrogen oxidation and cross-linking reaction, thereby increasing the softening point and wettability of the coated asphalt and reducing the content of quinoline insolubles.

[0040] After obtaining the reaction liquid after the second hydrogen oxidation and cross-linking reaction, the present invention cools the reaction liquid after the second hydrogen oxidation and cross-linking reaction to room temperature and then performs liquid phase volatilization to obtain coated asphalt for the negative electrode of a new energy battery.

[0041] In the present invention, the cooling is preferably natural cooling; the liquid phase volatilization is preferably vacuum negative pressure extraction; the vacuum degree of the vacuum negative pressure extraction is preferably 55 to 90 kPa, more preferably 60 to 80 kPa; the time of the vacuum negative pressure extraction is preferably 1 to 3 hours, more preferably 1.5 to 2.5 hours, and most preferably 2 hours.

[0042] In the present invention, the yield of the coated asphalt is preferably ≥44%, and more preferably 44-55%.

[0043] The present invention mixes and stirs a mixture of ethylene tar raw material and a crosslinking agent in an oxygen-containing atmosphere in a high-pressure reactor to cause a hydrogenation crosslinking reaction, then removes excess dissolved oxygen with a protective gas such as nitrogen and performs vacuum negative pressure extraction, and finally obtains coated asphalt. The preparation method has a short process flow, low operating cost, and short production time. The prepared coated asphalt has a high softening point, low quinoline insolubles, low coating thickness (≤20nm), high integrity (surface coverage ≥90%), and high density (density ≥0.92g / cm 3), high yield (44% ~ 55%), ethylene tar raw material cost is low, after being prepared into coated asphalt and used in lithium battery negative electrode, it plays a role in improving the initial efficiency (≥87%), reversible capacity (≥330mA·h / g), and cyclability (compared with the battery negative electrode without asphalt coating, the number of cycles of the battery negative electrode coated with asphalt is increased by ≥10%), which can solve the problem of ethylene tar resource utilization and the problem of improving the performance of lithium batteries.

[0044] The present invention also provides coated asphalt for the negative electrode of a new energy battery prepared by the preparation method described in the above technical scheme, wherein the softening temperature of the coated asphalt for the negative electrode of a new energy battery is ≥180°C, and the mass percentage of quinoline insoluble matter is ≤1%.

[0045] In the present invention, the softening temperature of the coated asphalt for the negative electrode of the new energy battery is ≥180°C, preferably 180-320°C, more preferably 183.5°C, 286.6°C or 204.8°C, and the mass percentage of quinoline insoluble matter is ≤1%, preferably ≤0.8%, more preferably 0.31%, 0.77% or 0.34%.

[0046] The present invention also provides the use of the coated asphalt for the negative electrode of a new energy battery described in the above technical solution in the negative electrode of a new energy battery.

[0047] The present invention has no special limitation on the application of the coated asphalt in the negative electrode of the new energy battery, and any application method known in the art may be used.

[0048] In the application example of the present invention, the preparation method of the negative electrode of the new energy battery is specifically as follows: the coated asphalt is dissolved in an organic solvent, and coated on the surface of the negative electrode carbon material by a solvent thermal synthesis method to form a coated asphalt layer to obtain a lithium battery negative electrode; the organic solvent is N,N-dimethylformamide (DMF); the mass of the coated asphalt is 4% of the negative electrode carbon material; the temperature of the solvent thermal synthesis method is 185°C. In the present invention, the coating thickness of the coated asphalt layer is preferably ≤20nm, the surface coverage is preferably ≥90%, and the density is preferably ≥0.92g / cm 3 .

[0049] In the present invention, the first efficiency of the negative electrode of the new energy battery is preferably ≥87%, and the reversible capacity is preferably ≥330 mA·h / g. Compared with the negative electrode of the new energy battery prepared without coating asphalt, the cycle number of the negative electrode of the new energy battery prepared by coating asphalt in the present invention is increased by ≥10%.

[0050] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0051] Example 1

[0052] Full-component ethylene tar (characteristics as shown in Table 1), naphthalene and anhydrous ethanol are mixed in a mass ratio of 100:1:0.1, and the resulting mixture is added to a high-pressure reactor, and stirred at 340°C at a speed of 200 r / min for 4 hours. While stirring, an oxygen-containing atmosphere (only air) with a flow rate of 2.5 L / min / kg (based on the mass of the mixture) is introduced and the pressure in the reactor is maintained at 0.8 MPa. Then, the oxygen-containing atmosphere in the high-pressure reactor is switched to a nitrogen atmosphere (based on the mass of the mixture, the nitrogen flow rate is 5 L / min / kg) and continued to be stirred at 200 r / min for 2 hours at 340°C and 1 MPa. The introduction of nitrogen atmosphere is stopped, and the reactor is naturally cooled to room temperature. Then, vacuum negative pressure extraction is performed to a vacuum degree of 55 kPa and maintained for 2 hours to volatilize the liquid phase in the reaction liquid in the reactor, and the remaining part is the coated asphalt (the yield is 44%).

[0053] Example 2

[0054] Heavy vinyl tar, acenaphthene and anhydrous ethanol are mixed in a mass ratio of 100:3:0.6, and the resulting mixture A is added to a high-pressure reactor, and stirred at 370°C at a speed of 100 r / min for 2 hours. While stirring, a mixed atmosphere of oxygen and air is introduced at a flow rate of 0.1 L / min / kg (based on the mass of the mixture) (the volume fraction of oxygen in the mixed atmosphere is 30%) and the pressure in the reactor is maintained at 1.5 MPa. Then, the oxygen-containing atmosphere in the high-pressure reactor is switched to a nitrogen atmosphere (based on the mass of the mixture, the nitrogen flow rate is 0.1 L / min / kg) and continued to be stirred at a speed of 100 r / min for 0.5 h at 370°C and normal pressure (0.1 MPa). The introduction of nitrogen atmosphere is stopped, and the reactor is naturally cooled to room temperature. Then, vacuum extraction is performed to a vacuum degree of 70 kPa and maintained for 1 hour to volatilize the liquid phase in the reaction liquid in the reactor, and the remaining part is the coated asphalt (the yield is 48%).

[0055] Example 3

[0056] Full-component ethylene tar (characteristics as shown in Table 1), azulene and anhydrous ethanol were mixed in a mass ratio of 100:2:0.3, and the resulting mixture was added to a high-pressure reactor and stirred at 380°C at a speed of 300 r / min for 3 hours. While stirring, a mixed atmosphere of oxygen and air was introduced at a flow rate of 5 L / min / kg (based on the mass of the mixture) (the volume fraction of oxygen in the mixed atmosphere was 50%) and the pressure in the reactor was maintained at normal pressure (0.1 MPa). Then, the oxygen-containing atmosphere in the high-pressure reactor was switched to a nitrogen atmosphere (based on the mass of the mixture, the nitrogen flow rate was 3 L / min / kg) and continued to be stirred at 300 r / min for 1 hour at 380°C and 1.5 MPa. The introduction of nitrogen atmosphere was stopped, and the reactor was naturally cooled to room temperature. Then, vacuum negative pressure extraction was performed to a vacuum degree of 90 kPa and maintained for 3 hours to volatilize the liquid phase in the reaction liquid in the reactor, and the remaining part was the coated asphalt (the yield was 55%).

[0057] Comparative Example 1 (without adding crosslinking agent)

[0058] Full-component ethylene tar (characteristics as shown in Table 1) was added into a high-pressure reactor and stirred at 350°C at a speed of 200 r / min for 3 h. While stirring, a mixed atmosphere of oxygen and air was introduced at a flow rate of 0.8 L / min / kg (based on the mass of full-component ethylene tar) (the volume fraction of oxygen in the mixed atmosphere was 10%) and the pressure in the reactor was maintained at 0.7 MPa. Then, the oxygen-containing atmosphere in the high-pressure reactor was switched to a nitrogen atmosphere (based on the mass of full-component ethylene tar, the flow rate of the nitrogen atmosphere was 3 L / min / kg) and continued to be stirred at a speed of 200 r / min for 1.5 h at 360°C and 0.5 MPa. The introduction of nitrogen atmosphere was stopped, and the reactor was naturally cooled to room temperature. Then, vacuum extraction to a vacuum degree of 80 kPa was performed and maintained for 2 h to volatilize the liquid phase in the reaction liquid in the reactor, and the remaining part was the coated asphalt (the yield was 35%).

[0059] Comparative Example 2 (Nitride atmosphere not introduced into the reactor)

[0060] Full-component ethylene tar (characteristics as shown in Table 1), naphthalene and anhydrous ethanol are mixed in a mass ratio of 100:2:0.4, and the resulting mixture is added to a high-pressure reactor, and stirred at 380°C at a speed of 300r / min for 1h. While stirring, a mixed atmosphere of oxygen and air is introduced at a flow rate of 4L / min / kg (based on the mass of the mixture) (the volume fraction of oxygen in the mixed atmosphere is 20%) and the pressure in the reactor is maintained at 1.0MPa. Then, the introduction of oxygen-containing atmosphere is stopped, and the reactor is naturally cooled to room temperature. Then, vacuum negative pressure extraction is performed to a vacuum degree of 70kPa and maintained for 2h to volatilize the liquid phase in the reaction liquid in the reactor, and the remaining part is the coated asphalt (the yield is 41%).

[0061] Comparative Example 3 (Direct negative pressure extraction without cooling the reactor)

[0062] Full-component ethylene tar (characteristics as shown in Table 1), naphthalene and anhydrous ethanol are mixed in a mass ratio of 100:2:0.2, and the resulting mixture is added to a high-pressure reactor, and stirred at 340°C at a speed of 200 r / min for 2 hours. While stirring, a mixed atmosphere of oxygen and air with a flow rate of 2.5 L / min / kg (based on the mass of the mixture) is introduced (the volume fraction of oxygen in the mixed atmosphere is 40%) and the pressure in the reactor is maintained at 1.5 MPa. Then, the oxygen-containing atmosphere in the high-pressure reactor is switched to a nitrogen atmosphere (based on the mass of the mixture, the flow rate of the nitrogen atmosphere is 2.5 L / min / kg) and stirring is continued at 340°C and 1.5 MPa at a speed of 200 r / min for 2 hours, and the introduction of nitrogen atmosphere is stopped. The liquid phase in the reaction liquid in the reactor is volatilized directly by vacuum negative pressure extraction to a vacuum degree of 90 kPa and maintained for 1 hour, and the remaining part is the coated asphalt (the yield is 32%).

[0063] Application Example 1

[0064] The coated asphalt (4% of the mass of the negative electrode carbon material) prepared in Example 1 was dissolved in an organic solvent (N,N-dimethylformamide, DMF), and coated on the negative electrode carbon material by solvent thermal synthesis at 185°C to obtain a new energy battery negative electrode.

[0065] Performance Testing

[0066] (1) The softening temperature of the coated asphalt is measured using a ring and ball softening point tester, and the quinoline insoluble matter is measured using GB / T2293-209 "Determination of quinoline insoluble matter".

[0067] The softening temperature of the coated asphalt prepared in Example 1 is 183.5° C., and the mass percentage of quinoline insoluble matter is 0.31%.

[0068] The softening temperature of the coated asphalt prepared in Example 2 is 286.6° C., and the mass percentage of quinoline insoluble matter is 0.77%.

[0069] The softening temperature of the coated asphalt prepared in Example 3 is 204.8° C., and the mass percentage of quinoline insoluble matter is 0.34%.

[0070] The softening temperature of the coated asphalt prepared in Comparative Example 1 was 133.2° C., and the mass percentage of quinoline insoluble matter was 2.47%.

[0071] The softening temperature of the coated asphalt prepared in Comparative Example 2 was 142.1° C., and the mass percentage of quinoline insoluble matter was 1.67%.

[0072] The softening temperature of the coated asphalt prepared in Comparative Example 3 was 138.9° C., and the mass percentage of quinoline insoluble matter was 1.63%.

[0073] (2) Figure 1 This is a physical picture of the coated asphalt prepared in Example 1 of the present invention; Figure 2 This is a transmission electron micrograph of the coated asphalt prepared in Example 1 of the present invention.

[0074] from Figure 1 and Figure 2 It can be seen that after the coated asphalt (4% by mass of the negative electrode carbon material) is dissolved in an organic solvent (DMF) and coated on the negative electrode carbon material by hydrothermal synthesis at 185°C, it is observed through an electron microscope that the coated asphalt has a uniform thickness (about 15 nm) on the surface of the negative electrode material, indicating that the coated asphalt prepared by the present invention has a lower coating thickness and a smooth coating surface.

[0075] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing coated asphalt for anode of a new energy battery, characterized in that: The following steps are involved: The ethylene tar raw material and the cross-linking agent are mixed, and a first hydrogen oxidation and cross-linking reaction is carried out in an oxygen-containing atmosphere to obtain a reaction liquid after the first hydrogen oxidation and cross-linking reaction; Transferring the reaction liquid after the first hydrogenation and cross-linking reaction into a protective gas atmosphere to carry out a second hydrogenation and cross-linking reaction to obtain a second hydrogenation and cross-linking reaction reaction liquid; After the reaction liquid after the second hydrogen oxidation and cross-linking reaction is cooled to room temperature, liquid phase volatilization is performed to obtain coated asphalt for the negative electrode of new energy batteries.

2. The preparation method according to claim 1, characterized in that: The ethylene tar raw material includes full-component ethylene tar or heavy ethylene tar.

3. The preparation method according to claim 1, characterized in that: The cross-linking agent comprises a mixture of dicyclic aromatic hydrocarbons and anhydrous ethanol; the dicyclic aromatic hydrocarbons comprise one or more of naphthalene compounds, acenaphthene compounds and azulene compounds.

4. The preparation method according to claim 1, characterized in that: The oxygen-containing atmosphere is a mixed atmosphere of oxygen and air; the volume fraction of oxygen in the mixed atmosphere is 0-50%.

5. The preparation method according to claim 1 or 4, characterized in that: Based on the total mass of the ethylene tar raw material and the cross-linking agent, the flow rate of the oxygen-containing atmosphere is 0.1 to 5 L / min / kg.

6. The preparation method according to claim 1, characterized in that: The temperature of the first hydrogenation and cross-linking reaction is 340-380° C., and the heat preservation time is 1-4 hours.

7. The preparation method according to claim 1, characterized in that: The protective gas is nitrogen or argon; based on the total mass of the ethylene tar raw material and the cross-linking agent, the flow rate of the protective gas is 0.1-5 L / min / kg.

8. The preparation method according to claim 1, characterized in that: The temperature of the second hydrogenation and cross-linking reaction is 340-380° C., and the heat preservation time is 0.5-2 h.

9. The coated asphalt for the negative electrode of new energy batteries prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The softening temperature of the coated asphalt used for the negative electrode of the new energy battery is ≥180° C., and the mass percentage of quinoline insoluble matter is ≤1%.

10. Application of the coated asphalt for the negative electrode of new energy batteries as claimed in claim 9 in the negative electrode of new energy batteries.

Citation Information

Cited By

  • A method for preparing modified pitch by upgrading pitch derived from semi-coke and modified pitch

    CN122521342A